Effect of Postoperative Methylprednisolone on Swelling and Pain After Mandibular Third Molar Surgery: A Randomized Controlled Trial - Tanumiharja, Leonardo Jaya Setiadi; Situmorang, Gabriella Debora Alvionita; Sumaji, Borman; Lesmana, Dian (Chakra Brahmanda Lentera Institute, 2026)
Background: Pain and swelling are common inflammatory complications following mandibular third molar surgery. Corticosteroids are widely used to control postoperative inflammation and improve patient comfort. However, evidence regarding the effectiveness of low-dose postoperative methylprednisolone, particularly at an 8 mg dose, remains limited, especially in low- and middle-income countries (LMICs). This study aimed to evaluate the effectiveness of an 8 mg dose of methylprednisolone on postoperative pain intensity and facial swelling following surgery. Methods: This study employed a parallel-group, two-arm randomized controlled trial design conducted in accordance with the CONSORT guidelines. A total of 30 patients who met the inclusion criteria were randomly assigned to either the intervention group (8 mg methylprednisolone) or the control group (standard care), with 15 participants in each group. The independent variable was methylprednisolone administration, while the dependent variables included pain intensity measured using the Visual Analog Scale (VAS) and facial swelling. Outcome assessments were performed on postoperative days 1, 3, and 7. Statistical analyses were used for independent t-tests. Results: Pain intensity was lower in the methylprednisolone group than in the control group at all postoperative time points, with large between-group effect sizes observed on day 1 (p = 0.003; Cohen’s d = 1.42), day 3 (p = 0.020; Cohen’s d = 1.36), and day 7 (p = 0.007; Cohen’s d = 1.18). Facial swelling also differed between groups, showing a lower degree of swelling in the methylprednisolone group during postoperative days 1–3 (p = 0.029; Cohen’s d = 0.98) and days 3–7 (p = 0.002; Cohen’s d = 0.87), indicating consistently large effects across outcomes. Conclusion: Low-dose methylprednisolone is statistically and clinically effective in reducing postoperative pain and swelling following surgery and may be integrated as a safe and cost-effective adjuvant therapy in postoperative dental care.